Pelatihan Bucket Snack Dan Branding Sebagai Alternatif Usaha Masyarakat Desa Keret Oleh Tim KKN 06 UNIPA Surabaya - Suyono Suyono; Rini Dwi A; Lailatul Badria; Isnaeni Himmatul A; Siti Nur Sholikha; Adinda Bintang A.I; Elsania Rahma L; Tinabul Munawaroh; Putri Cinthya M; M. Hifni Zakaria; Shinta Nuriyah Anwar; Nurrahma Enna D; Rangga Aji Perkasa (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
UMKM stands for Micro, Small and Medium Enterprises. This term refers to an enterprise or business that is relatively small in terms of number of employees, assets, and revenue compared to large companies. The problem of UMKM in Keret village is that the average people do business in the culinary field, due to the lack of modern business updates to improve economic, social and community welfare development in Keret village. The purpose of this research is to improve the knowledge, skills, and competencies of the community in economic development in Keret village. The method used in this research is descriptive qualitative, data collection techniques used in this research include starting activities, interviews, results and discussion, and conclusions. The results of this study indicate that we can improve the knowledge, skills, and competencies of the community in economic development in Keret village.